Penerapan Model Kooperatif Tipe Student Facilitator And Explaining Terhadap Pemahaman Konsep Fisika Siswa Kelas VIII MTsN Durian Tarung - Jannah, Raudhatul (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2018)
This research purpose to know whether cooperative model application with student facilitator and explaining type can increase physics concept comprehension of students compared with conventional mode at VIII class of MTsN Durian Tarung. This research is a quasi experiment research the randomized control group only design research program. The population of this research are all of VIII class of MTsN Durian Tarung Padang at 2016/2017 period consist of 8 classes. The getting data technique done is cluster random sampling. This is acquired by VIII1 class as experiment class and VIII3 class as control class. In this research acquired average value of physics student at cognitive side are 82,8 of experiment class and 79,0 of control class. Besed on data analysis have been gottenhave been gotten ,thitung = 2.008 and ttabel = 1.66 at the real level of 0.05. The result shows that t hitung > t tabel, until H0 rejected and H1 accepted. And the conclusion is comprehension physics concept by using student facilitator and explaining model advanced from concept comprehension by using conventional method in VIII class of MTsN Durian TarungÂ  at 2016/2017 period.